A Novel Emulsion-Based Mixture (EBM) Containing Ground Granulated Blast-Furnace Slag and Waste Alkaline Ca(OH)2 Solution. Issue 1 (March 2021) - Dulaimi, Anmar; Shanbara, Hayder Kamil; Al-Mansoori, Tariq
Abstract: Emulsion-based mixtures (EBM) attract less interest to use as a structural layer due to the weak mechanical performance, although it has environmental, economic, energy-saving benefits. Ground granulated blast-furnace slag (GGBS) activated by waste alkaline Ca(OH)2 solution is used in the present investigation to replace the conventional limestone filler in a new Emulsion-based mixture (EBM). The mechanical properties by means of indirect tensile stiffness modulus test of the EBM with the activated GGBS are examined and compared with those of EBM contained traditional limestone filler. The results indicate that the activated GGBS by waste alkaline Ca(OH)2 solution can enhance the ITSM in both early and mature ages. The hydration products can improve the bond strength inside the new EBM.